2021
DOI: 10.21203/rs.3.rs-776640/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does Environmental Decentralization Improve Regional Green Innovation? Evidence from China

Abstract: Green innovation is critical for sustainable development. The reform of environmental management system plays an important role in improving environmental pollution and technology progress. Working from a heterogeneous perspective, this study investigates the effects of different types of environmental decentralization on regional green innovation using statistical data from 30 provinces in China over the period of 2000–2015. The results show that environmental decentralization (ED) promotes regional green inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Wang, Y. and Feng, X. took the administrative approval policy as an example and found that the construction of the government system environment played an important role in enterprise innovation activities [16]. At the macro level, Yang, Z. and Qiu, G. revealed that deepening the reform of the fiscal decentralization system could mobilize the enthusiasm of local governments and further stimulate regional innovation output [17]. However, Zhang, L. and Ni, Z. argued that fiscal decentralization has a threshold effect on the concentration of scientific and technological talents and regional innovation efficiency, and when scientific and technological talents gather in an optimal range, the promotion effect on regional innovation efficiency is the largest [18].…”
Section: Government Behavior and Urban Innovationmentioning
confidence: 99%
“…Wang, Y. and Feng, X. took the administrative approval policy as an example and found that the construction of the government system environment played an important role in enterprise innovation activities [16]. At the macro level, Yang, Z. and Qiu, G. revealed that deepening the reform of the fiscal decentralization system could mobilize the enthusiasm of local governments and further stimulate regional innovation output [17]. However, Zhang, L. and Ni, Z. argued that fiscal decentralization has a threshold effect on the concentration of scientific and technological talents and regional innovation efficiency, and when scientific and technological talents gather in an optimal range, the promotion effect on regional innovation efficiency is the largest [18].…”
Section: Government Behavior and Urban Innovationmentioning
confidence: 99%